RELASI PENAFSIRAN AL-QUR’AN TERHADAP SIKAP SOSIAL-KEAGAMAAN SEKTARIAN ISLAM FUNDAMENTALIS DAN ISLAM MODERAT - Basrir Hamdani (Sekolah Tinggi Agama Islam (STAI) Sadra, 2018)
The main purpose of this paper is to show the relation between the interpretation of sacred texts, in this case the text of the Qur’an, and socio-religious attitudes of sectarian groups in Islam. This relation can be identified from the different characteristics of the social attitudes of religious people who are affiliated with certain groups in Islam which actually have different methods and styles of interpretation. This hypothesis is based on the principle that socio-religious attitudes are necessarily based on religious understanding, and the religious understanding must generate from interpretations of sacred texts, nor excluded in Islam with different methods and styles of interpretation of the Qur’anic texts by Muslims in different sects. This paper outlines two sects based on their methods and styles of interpretation, namely the Fundamentalists who tend to scripturalist-textualist methods and styles of interperetation and the Moderates with substantive-contextualist methods and styles. By analyzing the two methods of interpretation from the two groups, it is hoped that it can be used as a basis for identifying the socio-religious attitudes of Muslims and finding solutions to the negative implications in social life caused by these attitudes. The method that the author uses in presenting this paper is the analytical-critical-comparative method, which is to analyze critically the methods and styles of interpretation of the two religious groups and then with a comparative-critical approach the author tries to identify the socio-religious attitudes come from both of them, in the way to use it as a reference in finding solutions to solve the negative impacts of those attitudes in social life.